SINERGITAS INDUSTRI GULA DAN PETANI TEBU DALAM BAGI HASIL MELALUI PEMBERDAYAAN AVALIS KREDIT KETAHANAN PANGAN DAN ENERGI - Moh. Ramin; Norul; Mohammad Naufal Abdillah; Darul Hikmah; Aris Putra (ICO EDUSHA, 2022)
This paper discusses about the urgency or the importance of the role from Krebet Baru Sugar Factory as avalist in food and energy credits, and yo discuss the importance of this sugar factory as sugarcane processing related by profit sharing agreement with sugarcane farmers. The purpose of writing this journal to understand and analyze the urgency from Krebet Baru Sugar Factory as avalis in food and energy credits and to analyze about agreement result between sugary factory and sugarcane farmers by profit sharing agreement. Research methods used in the writing of this artikel is an empirical juridicial. The approach used in the juridicial sociological approach and a conceptual approach. The result of this artikel research found that sugar factory is an important part in food and energy credits because as avalist, this sugar factory play a role in choosing partner, determine the result of the sugarcane process and usually for credit payment. Sugar factory as sugarcane processing plays an important role in the process of planting sugar till harvesting sugarcane untill having a good sugarcane. Keywords: : avalist, profit sharing agreement, sugar factory   References Adrian, Sutedi. Buku Pintar Hukum Perseroan Terbatas. Jakarta: Raih Asa Sukses, (2015). Bahri, M., Kunaifi, A., & Ghufron, G. (2021). Agrowisata Pengembangan Sektor Pertanian Buah Melon Dalam Mitigasi Resesi Ekonomi DampaK PANDEMI COVID-19. Ekosiana: Jurnal Ekonomi Syariah, 8(2), 49–64. Bobo, Julian. Transformasi Ekonomi Rakyat. Jakarta: Pustaka Cidesindo, (2003). Brata, Asep Budi, Upaya BI dalam mendongkrak Peningkatan Penyaluran Kredit Program Melalui Kemitraan Strategis, Pada http://www.rmol.co/read/2011/12/01/47602/Upaya-BI-dalam Mendongkrak-Peningkatan-Penyaluran-Kredit--Program-MelaluiKemitraan-Strategis-. Direktorat Jenderal Prasarana Dan Sarana Pertanian, Kementerian Pertanian. Pedoman Teknis Kredit Ketahanan Pangan dan Energi Tahun 2015. Jakarta: (2015). Elsi, Kartika Sari dan Simangunsong Advendi. Hukum Dalam Ekonomi. Jakarta: Grasindo, (2007). Kansil, C.S.T. Pengantar Ilmu Hukum dan Tata Hukum Indonesia. Jakarta: PN Balai Pustaka, 1984. Soemitro, Ronny Hanitijo. Metodologi Penelitian Hukum dan Jurimerti. Jakarta: Ghalia, 1988. Notoatmodjo, Soekidjo. Pendidikan dan Perilaku Kesehatan. Jakarta: Rineka Cipta, (2003). Kelompok Gapoktan ,Demonstration Plot (DEMPLOT), dalam. https://gapoktansaluyu.wordpress.com/2012/02/04/demontration-plotdemplot/. Diakses 07 Agustus 2016. Kolopaking, Lala M. Kemitraan Dalam Pengembangan Usaha Ekonomi Skala Kecil/ Gurem. Jakarta: Makalah Lokakarya Nasional Pengembangan Ekonomi Daerah Melalui Sinergitas Pengembangan Kawasan, (2002). Kunaifi, A., Fikriyah, K., & Aliyah, D. (2021). How Do Santri, Local Wisdom, and Digital Transformation Affect Community Empowerment? Ilomata International Journal of Social Science, 2(4), 246–257. https://doi.org/10.52728/ijss.v2i4.359 Kunaifi, A., Rahman, F., & Dwiaryanti, R. (2021). The Philosophy and Authentication of Welfare Equalization in the Islamic Economy. Jurnal Kajian Peradaban Islam, 4(2), 54–62. https://doi.org/10.47076/jkpis.v4i2.67 Markus, Muda. Perpajakan Indonesia Suatu Pengantar. Jakarta: Gramedia Pustaka Utama, 2005. Aqimuddin, Eka An, dan Marye Agung Kusmagi. Tip Hukum Praktis: Masalah Seputar Bisnis. Jakarta: Raih Asa Sukses, (2010). Pundjul, Putranto. Faktor Pendukung Rendemen Tebu. Surabaya: Indocode Surya, (2014). Pusat Penelitian Perkebunan Gula Indonesia. Konsep Peningkatan Rendemen. Pasuruan, 1987. Peraturan Perundang-undangan Soekanto, Soerjono dan Sri Mamudji. Metode Penelitian Hukum. Jakarta: Ghalia Indonesia, (1992). Soemitro, Ronny Hanitijo. Metode Penelitian Hukum dan Yurimetri. Jakarta: Ghalia Indonesia, 1990. Martodireso, Sudadi dan Ir. Widada Agus Suryanti, MM. Agribisnis Kemitraan Usaha Bersama (Upaya Peningkatan Kesejahteraan Petani). Jakarta: Penerbit Kanisius, (2000). Undang-Undang Republik Indonesia Nomor 3 Tahun 2014 tentang Perindustrian. Peraturan Daerah Provinsi Jawa Timur Nomor 17 Tahun 2012 tentang Rendemen Tebu dan Hablur Tanaman Tebu. Peraturan Menteri Pertanian Nomor: 33/Permentan/OT.140/7/2006 tentang Pengembangan Perkebunan Melalui Program Revitalisasi Perkebunan. Yusri, Perlindungan Hukum Terhadap Usaha Mikro Kecil dan Menengah dalam Perspektif keadilan ekonomi, Jurnal Ilmu Hukum, Volume 16, Nomor 1 (2014) Undang Undang Nomor 3 Tahun 2014 Tentang Perindustrian, Pada Https://Peraturan.BPK.go.id